Analisis Efisiensi Industri Perbankan di Indonesia Dengan Pendekatan Data Envelopment Analysis (Dea) Dan Faktor-Faktor Yang Mempengaruhinya - Yusniar, Meina Wulansari (Jurnal Manajemen Bisnis, 2011)
The sffeciensy lavel of the banking industry is themost important indicator to identify the soundess of banking system. Efficiency is a theoretically parameter that can be used as base of all performance in bank. This research using non parametric frontier approach, DEA, to analyze bank efficiency in Indonesia’s banking industry using annual sample. We use price of labor, price of fund, and Total deposits as controlles input variabel and total loans and income as output variabel. We found that mixing bank are the most efficiency group in the last seven year from 2002-2008. We also excamine the relationship between Size, CAR, NPL, LDR, status Go Public and bank efficiency. Using panel methodology and OLS as a method of estimation, the results provide evidence of a positive significant relationship between Size, CAR, LDR and bank afficiency while status Go public negatively significant affect bank afficiency. The study, however, could not provide a significant relationship between NPL and bank efficiency. These result are consistent with prior empirical studies.